2018
DOI: 10.1387/ijdb.170301mn
|View full text |Cite
|
Sign up to set email alerts
|

A snail tale and the chicken embryo

Abstract: Some 25 years ago, a clone was identified that contained the chicken Slug sequences (now called Snail2 ). How could we anticipate at that time how much the chick embryo would help us to understand the ins and outs of cell migration during development and in disease? Indeed, the chick embryo helped us identify Snail2 as the first transcription factor that could induce the epithelial-mesenchymal transition (EMT), key for the migration of embryonic and cancer cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…By contrast, a number of comparative studies performed in several group of animals (chordates, insects, nematodes…) have revealed that development is flexible and that formation of homologous characters may rely on different mechanisms, a process known as developmental system drift (DSD) (3,(7)(8)(9)(10)(11)(12)(13)(14). In some cases, key GRN nodes have changed (for example the role of Snail/Slug genes in vertebrate neural crest (15)). Focusing on GRN edgesgene expression regulationvarious situations have been described, and conservation of CRM sequence at the DNA level does not necessarily correlate with conservation of activity.…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, a number of comparative studies performed in several group of animals (chordates, insects, nematodes…) have revealed that development is flexible and that formation of homologous characters may rely on different mechanisms, a process known as developmental system drift (DSD) (3,(7)(8)(9)(10)(11)(12)(13)(14). In some cases, key GRN nodes have changed (for example the role of Snail/Slug genes in vertebrate neural crest (15)). Focusing on GRN edgesgene expression regulationvarious situations have been described, and conservation of CRM sequence at the DNA level does not necessarily correlate with conservation of activity.…”
Section: Introductionmentioning
confidence: 99%
“…2 D). The first group includes genes that are associated between NC and a closely-related cell type in only one organism (e.g., NC and neural plate in frog: sox2, sox3 (neural plate markers [ 26 ]), snai2 (neural crest marker [ 27 ]) , hes1, zic1 (neural border markers [ 20 ]); NC and midhindbrain in mice: fodx3, gadd45a (neural crest marker [ 28 ]) , mdk, ptn (neural crest-derived neurons markers [ 29 ])). If this gene expression signature was the consequence of the evolutionary divergence of function, this could be studied using the scRNA-seq of the ancestor organisms.…”
Section: Resultsmentioning
confidence: 99%
“…Researchers in the field of EMP have employed various animal models, including as C. elegans, Drosophila Melanogaster, chick embryos, zebrafish and mice to study the in vivo dynamics of phenotypic plasticity in developmental EMT and cancer EMP (Jimenez et al, 2016;Gómez-Cuadrado et al, 2017;Nieto, 2018;Stuelten et al, 2018;Campbell et al, 2019). Genetically engineered mouse models and patient-derived xenografts (PDXs) have been observed to recapitulate metastatic and organ homing properties similar to clinical specimens (Sikandar et al, 2017).…”
Section: Current Modalities To Investigate Plasticitymentioning
confidence: 99%